Prognostic significance of autophagy-related genes Beclin1 and LC3 in ovarian cancer: a meta-analysis - Chen, Xinbei (J Int Med Res, 2020)
OBJECTIVE: Beclin1 plays a central role in the activation of the autophagy signaling pathway. Beclin1 and LC3-related proteins are involved in the initial steps of autophagy, which are closely related to the occurrence and development of tumors. The current meta-analysis aimed to clarify the correlation between expression of Beclin1 and LC3 and prognosis of ovarian cancer. METHODS: We searched PubMed, Embase, The Cochrane Library, Web of Science, and CNKI using predefined selection criteria. Pooled hazard ratios and relative risks with 95% confidence intervals were used to evaluate the correlation between autophagy-related genes Beclin1 and LC3 and overall survival (OS), progression-free survival (PFS), and International Federation of Gynecology and Obstetrics (FIGO) stage. RESULTS: In total, 1497 patients from 10 articles were enrolled in this meta-analysis. Expression of Beclin1 was significantly correlated with improved OS and PFS, and increased expression of Beclin1 was correlated with early FIGO stage, but not with lymph node metastasis or histological grade. No association was found between LC3 expression and prognosis in patients with ovarian cancer. CONCLUSIONS: Expression of Beclin1 is an independent risk factor for the progression of ovarian cancer. Thus, Beclin1 is a promising indicator in predicting prognosis in patients with ovarian cancer.